Understanding the Use of Social Media by MSMEs in Bali Province during the Covid 19 Pandemic - Si Agung Candra Arum Sari Dewi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The Large-Scale Social Restriction Policy (PSBB) is an obstacle for MSMEs actors so that there is a transition from offline to online business.MSMEs need to adapt to the use of social media as a tool to reach a wider range of consumers.the number of MSMEs in Bali is still low in utilizing digital platforms. Therefore, this research will recognize the factors MSMEs adopted social media during pandemic Covid-19.This research was conducted qualitatively with the library research method. In the literature review, the factors found are perceived usefulness and perceived ease of use in the technology acceptance model. In addition, there are other factors, namely compatibility and leadership support. MSMEs that still survive and have taken advantage of social media that are related to the perceived usefulness and perceived ease of use factors because MSME actors only use social media after feeling that social media during the pandemic is more profitable compared to limited offline sales. The SMEs leaderships support factor which is training for MSMEs will help employees to make digital platforms a tool that supports business activities during the pandemic.